Risks, challenges and socioeconomic impacts of quarrying on rural livelihoods in Tanzania - Felician Andrew Kitole; Venance Ephraim Kalumanga; Dennis Werner Hyera; Erick Mchuma Evason (Cogent Social Sciences)
Quarrying serves as both a lifeline and a challenge for rural communities in Tanzania, where livelihoods depend on extracting stone amidst environmental and economic hardships. This study examines the risks, challenges and socioeconomic impacts of quarrying on 300 households across Mzumbe, Mlali and Melela villages using a quantitative research approach. Through surveys and statistical analyses—including descriptive statistics, K-means clustering and principal component analysis—the study explores participation patterns, sociodemographic influences, environmental awareness and perceived risks. Results show that males (64.6%) are more involved in quarrying than females (70.6%), with significant links to marital status, age and employment status. Quarrying households earn higher incomes but also face financial burdens and higher dependency ratios, indicating that despite increased earnings, their economic pressures remain high due to larger household sizes and greater financial responsibilities. Major challenges include health risks (70%), environmental degradation (65%) and income instability (62%), with 39% of households uncertain about their future in quarrying. While environmental awareness, particularly regarding deforestation, is high, barriers such as lack of capital and equipment hinder participation, especially among poorer households. Despite these risks, economic necessity drives many to continue quarrying as a primary source of income. To mitigate its negative impacts, the study recommends formalizing the sector to improve safety regulations, enhancing education to expand livelihood opportunities, providing financial support to address capital constraints and promoting sustainable practices through environmental education. Addressing these challenges is crucial for improving the well-being, economic stability and long-term sustainability of rural households engaged in quarrying in Tanzania.